Modélisation des savoirs dans la classe en didactique de la physique - Andrée Tiberghien (Nantes Université, 2017)
In this paper, we account for a way of modeling classroom practices from a didactic point of view in the case of the teaching of physics. Then we draw certain proposals for a comparative analysis of school practices. Our modeling is based on a pragmatic approach of classroom practices. In a first step, the Theory of joint action in didactics is succinctly introduced in connection with several other theoretical choices concerning learning, knowledge and the necessity of different temporal scales. In a second step, the methodological tools of modeling are introduced with some examples of analyzes that illustrate the links between theoretical framework and methodological tools. These tools are aligned with certain research questions related to classroom practices. Two types of tools are proposed: one, at the mesoscopic level, allows to structure a series of sessions of a teaching sequence; the other, at the microscopic level, allows to analyze the pieces of knowledge at stake in the classroom discourses. In the conclusion, we draw some proposals for a comparative analysis based on the theoretical and methodological framework presented, in particular the comparison of time scales and units of analysis at the meso and microscopic level.